Reticulate evolution and taxonomic concepts in the Ranunculus auricomus complex (Ranunculaceae): insights from analysis of morphological, karyological and molecular data - Hörandl, Elvira (2009)
The Ranunculus auricomus complex is an interesting model system for studying the evolution and diversity of apomictic polyploid complexes. It comprises hundreds of agamospecies, usually referred to two distinct morphotypes (traditionally named “R. auricomus” and “R. cassubicus”) which are connected by several intermediate forms. Here we try to elucidate the evolution of apomictic “cassubicus” morphotypes and we test criteria for different classification concepts by combining the information of molecular phylogenetic, morphological, karyological and population genetic data (AFLPs, amplified fragment length polymorphism). Phylogenetic analysis based on sequences of the nrDNA ITS and plastid data (matK, trnk, psbJ-psbA) suggest a deep split between the diploid sexual species R. notabilis (“auricomus” morphotype) from the closely related allopatric taxa R. cassubicifolius and R. carpaticola (“cassubicus”). The apomictic “cassubicus” morphotypes are not monophyletic, as one, R. hungaricus, groups with R. notabilis, which may be due to hybrid origin. Morphometric studies and ploidy level determinations via Feulgen densitometry show a transition from 4x R. hungaricus to the 6x apomictic hybrid derivatives of R. cassubicifolius and R. carpaticola. In two accessions, AFLPs and flow cytometric data suggest local gene flow among different apomictic polyploid morphotypes. Frequent facultative sexuality of apomicts may increase genetic diversity by continuous formation of new cytotypes, local hybridization and introgression, which obstructs the fixation of distinct agamospecies. We conclude that “R. cassubicus” and “R. auricomus” cannot be regarded as species but should be treated as either informal groups, or as (notho)taxa at the sectional level. To reflect the different evolutionary processes involved, we propose a separate classification of the sexual species, R. notabilis and the closely related species pair R. cassubicifolius and R. carpaticola. Based on these well-defined biological species, the apomictic biotypes can be classified as nothotaxa.